INTEGRATION OF WEB-BASED ARABIC LEARNING IN INTERNATIONAL CLASS STUDENTS OF UIN WALISONGO SEMARANG - Inayah, Inayah; Sa’adah, Fina; Latifah, Mila (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
It’s necessary that the university be able to meet the standards of international competitiveness in terms of curriculum, programs and interactions between students using the international languages. It’s from the existence of this criterion that at State Islamic University Walisongo there has been the International Class Program (ICP) in the Faculty of Education and Teacher Training (FITK) since 2021. One of the forms of the education unit is the use of the "Arabic Online" which was started by the Saudi Electronic University and this program can be accessed via the web https://arabic.seu.edu.sa/ or a smartphone. Lists included in this program are placement test, start of study program, selection of subjects according to their ability level, independent study sessions and direct teaching sessions. These specifications are appropriate to the Walisongo’s vision which is the First of the Islamic research University based on the unity of sciences for humanity and civilization in 2038. The research purposes are: describe Arabic Online Program, and describe Web-based Arabic Learning in ICP students. This study is a descriptive qualitative research. The method of data collection used is observation, documentation and interview. The data analysis used is the triangulasi technique of data reduction, display, and conclusion. The result of the research is that the "Arabic Online" as one of the Arabic language learning Program based on the web has positive effects in upgrading students' language competencies, especially for the skill of listening, speaking, reading, writing and grammar.